PENGARUH PENGALAMAN ORGANISASI, SOFT SKILL DAN EFIKASI DIRI TERHADAP KESIAPAN KERJA CALON LULUSAN UNIVERSITAS YPPI REMBANG - Eldhen Florenhe Ardelta; Agustina Widodo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
To compete in the job market in the era of globalization and technological innovation, university graduates must be as well prepared as possible to enter the workforce. The purpose of this study was to examine how organizational experience, soft skills, and self-efficacy influence the readiness of prospective YPPI Rembang University graduates to enter the workforce. Purposive sampling was used to select a sample from a population of 134 students in this quantitative study. A Likert-scale questionnaire was used to collect data, and multiple linear regression was used for analysis. The results showed that self-efficacy and organizational experience both had positive and significant effects on job readiness, while soft skills had a beneficial but negligible impact. These three independent variables explained 78.9% of the variation in job readiness, according to an Adjusted R2 value of 0.789; other factors outside the model explained the remaining 21.1%.